Laboratory Research On Airborne Infection Control in Hospital Operating Rooms - Harsem, Trond Thorgeir; Melikov, Arsen; Venås, Bård; Flaarønning, Haakon; Jablonskis, Marius; Mathisen, Hans Martin (ASHRAE journal, 2025)
Hospital operating rooms (ORs) are highly used facilities that are classified as having ultraclean environments. Yet, surgical site infections following surgical procedures pose a significant challenge in Norway and globally.1 Between 2018 and 2022, a comprehensive analysis of surgical data from Norway and 12 European Union member states revealed 19,680 postoperative surgical site infections (SSI).2This article explores the research performed in a cutting-edge hospital operating room in Norway and how it is being used to help reduce SSIs.